If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -20 = 7x + -4 Reorder the terms: -20 + 3x = 7x + -4 Reorder the terms: -20 + 3x = -4 + 7x Solving -20 + 3x = -4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -20 + 3x + -7x = -4 + 7x + -7x Combine like terms: 3x + -7x = -4x -20 + -4x = -4 + 7x + -7x Combine like terms: 7x + -7x = 0 -20 + -4x = -4 + 0 -20 + -4x = -4 Add '20' to each side of the equation. -20 + 20 + -4x = -4 + 20 Combine like terms: -20 + 20 = 0 0 + -4x = -4 + 20 -4x = -4 + 20 Combine like terms: -4 + 20 = 16 -4x = 16 Divide each side by '-4'. x = -4 Simplifying x = -4
| 2x+x+2(2)+89=180 | | 15r^2=-7r+4 | | 7x-37=29+4x | | 30+8y=-7y | | (14x-22)(x+11)=240 | | 4y-12=14 | | 2y-7x=-10 | | 3x+2[x+7]-5=4[x+3]-3[x+1] | | 20x-15=-8 | | 8w^2-18+9= | | 6H+H-20=44-H | | 2[4+2(5-x)-2x]=4(7-2x) | | 6H+H-20=44 | | 2z^2=5z-2 | | 2x+9x+12=6 | | 2x^2-4y=8 | | y-7=3(x-6) | | 8x-28=16+6x | | 70x+25(80)=60x+60(80) | | 4(1+X)=2(2+X) | | 14=50x | | x+7=-61 | | -2x-8=-13x-4 | | -5=25x | | -16x=224 | | 111n-9=5n+27 | | 15*15x=144 | | (2x+3)x(3x-6)= | | 1.5(2a+1)=5(0.5a+0.3)+0.1 | | (0.8g+0.6-0.3)=(0.1-0.2h+0.8g) | | -x-5=3x+19 | | x^2+4*x-7=2*x-4 |